PERAN UMKM DALAM MEMPERTAHANKAN EKONOMI JAWA TIMUR SELAMA PANDEMIC COVID – 19 - Khuriyatul Mutrofin; Adam Nur Muhammad; Mahmud (El-Idaarah, 2021)
Micro, Small and Medium Enterprises are productive businesses owned and managedby individuals and business entities that have met the criteria as micro enterprises. Thepurpose of this paper is to see how far the potential of East Java MSMEs is able tosurvive in the midst of the onslaught of the Covid 19 pandemic that has occurred sincethe beginning of 2020. This research method is descriptive qualitative using secondarydata from research results, references and online news related to this research.According to Law no. 20 of 2008, the definition of MSME is a trading business managedby individuals or business entities that refers to productive economic businesses with the criteria stipulated by Law Number 20 of 2008. As regulated in legislation no. 20 of2008, according to the definition of MSMEs, the criteria for MSMEs are distinguished,respectively, including micro, small and medium enterprises. According to data releasedby Bank Indonesia (BI), the number of MSME actors in Indonesia currently reaches56.54 million units or 99.99% of the total business actors. In other words, Micro, Smalland Medium Enterprises (MSMEs) are the largest business group in Indonesia. Fromthis data, we can understand that Micro, Small and Medium Enterprises (MSMEs) havea very important role for the economy in Indonesia. In addition, this business group hasalso been able to survive the various economic turmoil that has been experienced byIndonesia so far, including the slump in the Indonesian economy in the last year due tothe onslaught of the Covid-19 pandemic.